(untitled) - Desai, Anil (San Francisco, 2001)
The new edition of the MCSE: Windows 2000 Directory Services Administration Study Guide is the ultimate study tool for exam 70-217, Implementing and Administering a Microsoft® Windows® Directory Services Infrastructure. Working in conjunction with our team of expert authors, we've made significant enhancements to the study guide based on reader and instructor feedback gathered over the past year. So what's new? We've replaced virtually all of the review and bonus exam questions with more challenging questions that better reflect the difficulty of the actual tests; we've added Real World Scenarios to provide additional insights into the intricacies of implementing Microsoft's Directory Services in enterprise networks; and we've added Exam Essentials sections to each chapter, where key exam topics are highlighted. All this in addition to general improvements to the overall instructional quality of the book
Keywords: Electronic data processing personnel,Directory services (Computer network technology); Certification,Examinations